Internet of things architecture : Current challenges and future direction of research - Basiron, Halizah; Mohd Aboobaider, Burhanuddin; Mohammed, Ali Abdul-Jabbar; Ismail, Ronizam (Research India Publications, 2017)
The Internet of Things (IoT) is a new paradigm that can enable collecting and exchanging data that have never been attainable before.It able to communicate and report user’s information in a more secure way.The reports of Cisco analysts estimate that the IoT will have more than 50 billion of smart sensors and other smart devices or gadgets,all connecting and communicating real time data on the internet by 2020.This will provide deeper insights with data analytics using the IoT paradigm to establish new business,enhance productivity and efficiency,and develop innovative revenue streams.Furthermore,the IoT architecture may combine features and technologies suggested by various methodologies.Since,this architecture is designed where the digital and real worlds are integrating and interacting constantly,various technologies are merged together to form IoT,such as; sensing technologies,pervasive computing,ubiquitous computing,internet protocols,smart objects,embedded parts,etc.When a regular device utilizes intelligent agents,it becomes a smart object.In this way,it is not only used to gather the environment information or interact with the physical world,yet more than that,it must be interconnected with various network devices to exchange and communicate data over the internet. Therefore,the significant measure of available data which is produced by the immense number of interconnected devices will offer opportunities to generate information that will deliver significant benefits to the economy, environment,individuals,and society.In this paper,we present past,current,and future direction of IoT.This paper provides overview and clear examination of the IoT architecture paradigm with the description of its fundamental requirements along with the implementation challenges and future directions.Thus,it will open issues that will face the IoT by new world generation.